- #1

- 734

- 0

why does (-y/x^2)dx+(1/x)dy=d(y/x)?

You are using an out of date browser. It may not display this or other websites correctly.

You should upgrade or use an alternative browser.

You should upgrade or use an alternative browser.

- Thread starter asdf1
- Start date

- #1

- 734

- 0

why does (-y/x^2)dx+(1/x)dy=d(y/x)?

- #2

lurflurf

Homework Helper

- 2,440

- 138

because

[tex]df=\frac{\partial f}{\partial x}dx+\frac{\partial f}{\partial y}dy[/tex]

and

[tex]\frac{\partial}{\partial x}(\frac{y}{x})=\frac{-y}{x^2}[/tex]

and

[tex]\frac{\partial}{\partial y}(\frac{y}{x})=\frac{1}{x}[/tex]

[tex]df=\frac{\partial f}{\partial x}dx+\frac{\partial f}{\partial y}dy[/tex]

and

[tex]\frac{\partial}{\partial x}(\frac{y}{x})=\frac{-y}{x^2}[/tex]

and

[tex]\frac{\partial}{\partial y}(\frac{y}{x})=\frac{1}{x}[/tex]

Last edited:

- #3

- 734

- 0

- #4

- 734

- 0

it's hard to understand...

- #5

Astronuc

Staff Emeritus

Science Advisor

- 19,175

- 2,618

If one has done the derivative of a product, then one knows -

[tex]\frac{d}{dx}(u(x)*v(x))= v(x) * \frac{d}{dx} u(x) + u(x) * \frac{d}{dx} v(x)[/tex]

This can be verified with the definition of the derivative.

Then [tex]\frac{d}{dx}(\frac{1}{x})= -\frac{1}{x^2} [/tex],

which can also be shown using the definition of the derivative.

- #6

matt grime

Science Advisor

Homework Helper

- 9,395

- 4

asdf1 said:it's hard to understand...

no it isn't, it's a definition. if you don't know what the definitions are then of course it will seem hard, but this is exactly what the notation means.

- #7

HallsofIvy

Science Advisor

Homework Helper

- 41,833

- 963

Yes, it is clear that [tex]d\frac{y}{x}= -\frac{y}{x^2}dx+ \frac{1}{x}dx[/tex] because [tex]\frac{d(\frac{a}{x})}{dx}= -\frac{a}{x^2}[/tex] for any constant a and [tex]\frac{d(\frac{y}{a})}{dy}= \frac{1}{a}[/tex] for any constant a.

**But** how would you go from [tex]-\frac{y}{x^2}dx+ \frac{1}{x}dx[/tex] to [tex]d{(\frac{y}{x})}[/tex]? That, I think, is the question being asked and I'll bet it's in your textbook: look under "exact differentials" or "integrals independent of path". (Actually, going that direction gives a more general answer- you have a "constant of integration".)

You know that [tex]dF(x,y)= \frac{\partial F}{\partial x}dx+ \frac{\partial F}{\partial y} dy[/tex]. So whatever F is, if [tex]dF= -\frac{y}{x^2}dx+ \frac{1}{x}dx[/tex] then we must have [tex]\frac{\partial F}{\partial x}= -\frac{y}{x^2}[/tex] and [tex]\frac{\partial F}{\partial y}= \frac{1}{x}[/tex].

In particular, taking the anti-derivative of [tex]\frac{\partial F}{\partial x}= -\frac{y}{x^2}[/tex] , we have (remembering that the partial derivative treats y like a constant), [tex]F(x,y)= \frac{y}{x}+ g(y)[/tex] because the anti-derivative of [tex]\frac{a}{x^2}= ax^{-2}[/tex] is -ax^{-1} and here a is -y. Notice that g(y)! That's the "constant" of integration- no matter what function of y g is, taking the partial derivative with respect to x is 0.

Now, differentiate**that** with respect to y: [tex]\frac{\partial \frac{y}{x}+ g(y)}{\partial y}= \frac{1}{x}+ g'(y)[/tex] (Since g is a function of y only, the derivative of g is an ordinary derivative). Now compare that with [tex]\frac{\partial F}{\partial y}= \frac{1}{x}[/tex]. We must have [tex]\frac{1}{x}+ g'(y)= \frac{1}{x}[/tex] which just tells us that g'(y)= 0 so g(y) really is a constant!

[tex]F(x,y)= \frac{y}{x}+ C[/tex] or [tex]d(\frac{y}{x}+C)= -\frac{y}{x^2}dx+ \frac{1}{x}dx[/tex]. Of course, your example is taking C= 0.

You know that [tex]dF(x,y)= \frac{\partial F}{\partial x}dx+ \frac{\partial F}{\partial y} dy[/tex]. So whatever F is, if [tex]dF= -\frac{y}{x^2}dx+ \frac{1}{x}dx[/tex] then we must have [tex]\frac{\partial F}{\partial x}= -\frac{y}{x^2}[/tex] and [tex]\frac{\partial F}{\partial y}= \frac{1}{x}[/tex].

In particular, taking the anti-derivative of [tex]\frac{\partial F}{\partial x}= -\frac{y}{x^2}[/tex] , we have (remembering that the partial derivative treats y like a constant), [tex]F(x,y)= \frac{y}{x}+ g(y)[/tex] because the anti-derivative of [tex]\frac{a}{x^2}= ax^{-2}[/tex] is -ax

Now, differentiate

[tex]F(x,y)= \frac{y}{x}+ C[/tex] or [tex]d(\frac{y}{x}+C)= -\frac{y}{x^2}dx+ \frac{1}{x}dx[/tex]. Of course, your example is taking C= 0.

Last edited by a moderator:

- #8

- 734

- 0

thank you! :) that clears a lot of things up~

Share: